SARS CoV-2 (COVID-19) and Its Biological Effects - Temizkan, Nuray; Gök, Özlem; Aslan, Abdullah (Soner ÖZGEN, 2024)
Severe Acute Respiratory Syndrome Coronavirus-2 (SARS CoV-2), the causative agent of coronavirus disease 2019 (COVID-19), has caused an epidemic that the world is struggling with and has initiated a global pandemic. Since the beginning of the epidemic in 2019, many countries, including Turkey, have developed various vaccines and treatment methods to protect against COVID-19 disease. All studies during the pandemic aimed to activate the body’s immune system against SARS CoV-2 infection and to control the epidemic. The goal of vaccines is to create antibody memory specific to the structural proteins of SARS CoV-2. In addition, treatment techniques prevent the accumulation of products that cause tissue damage, such as cytokine storm, which is released as a result of excessive immunity against this virus in the body.

Koronavirüs hastalığı 2019 (COVID-19)’un etkeni olan Ağır Akut Solunum Sendromu Koronavirüs-2 (SARS CoV-2), dünyanın mücadele ettiği bir salgına neden olmuş ve küresel çapta bir pandemiyi başlatmıştır. Salgın başlangıcı olan 2019’dan beri Türkiye de dahil birçok ülke COVID-19’dan korunmak için çeşitli aşılar ve tedavi yöntemleri geliştirmiştir. Pandemi boyunca yapılan tüm çalışmalar SARS CoV-2 enfeksiyonuna karşı vücudun bağışıklık sistemini aktifleştirmeyi ve salgını kontrol altına almayı amaçlamıştır. Aşıların hedefi SARS CoV-2’nin yapısal proteinlerine spesifik antikor hafızası oluşturmaktır. Ayrıca tedavi teknikleri de vücutta bu virüse karşı gelişen aşırı bağışıklık sonucu salınan sitokin fırtınası gibi doku hasarı meydana getiren ürünlerin birikimine engel olmayı sağlamaktadır.
SARS CoV-2 (COVID-19) ve Biyolojik Etkileri
Keywords: Proteomics and Intermolecular Interactions; Proteomik ve Moleküller Arası Etkileşimler; Genetic Immunology; Genetik İmmünoloji; Genomics; Genomik